Butterfly foraging strategies and their interactions with some selected nectar plants: Butterfly foraging strategies and interactions with nectar plants (Dhaka University Journal of Biological Sciences, 2026)
An attempt was made to determine foraging strategies of butterflies, foraging time budget, duration of foraging and nectar plants interactions for one year (2015-2016) in a semi-urban forest and urban green habitat. Total thirteen butterfly species were selected to find revealed interspecific variations in time budget of foraging on specific flower, which served as a proxy for pollination efficiency. The Eurema hecabe (Pieridae) 390 ± 6.37 and Tirumala limniace (Danaidae) 245 ± 1.90 showed highest and lowest foraging time budget was in Spindasis lohita (Family: Lycaenidae) 16 ± 1.58. In contrast, Spindasis lohita demonstrated the significance foraging with longer duration 389.75 ± 3.73 seconds per visit on Micromelum minutum.  When the visit numbers of foraging were lower the butterfly usually foraged with a longer duration. Danaus chrysippus (Family: Danaidae) was identified as the most significant pollinator with a longer foraging duration (21.3 ± 1.98) on the flower of Helianthus debilis. The foraging time budget of this species was varied in different nectar plants. The nectar plants Lantana camara was widely used by Tirumala limniace (Danaidae), Pelopides matheas (Hespiridae) and Junonia almana (Nymphalidae).  The foraging efficiency on nectar plants was higher those had longer proboscis e.g. Pachliopta aristolochiae (15.21 ± 9.92) and D. chrysippus (12.45 ± 0.5); had a selective advantage when foraging the nectar plants. The P. mathias (8 ± 1.45) and Lampides boeticus (7.16 ± 0.5) had shorter proboscis compared to others. The results of this study offers a valuable tool for identifying key pollinators butterfly species. This study will enhance ecosystem services and pollinator conservation planning through preserve the plant species and their interaction with butterfly.Dhaka Univ. J. Biol. Sci. 35(1): 47-67, 2026 (January)